Perceived Project Value, Opportunistic Behavior, Interorganizational Cooperation, and Contractor Performance - Ntayi, Joseph Mpeera; Rooks, Gerrit; Eyaa, Sarah; Qian, Cheng (Journal of African Business, 2010)
Predictors of contractor performance have attracted the attention of researchers in the developed world. However, research from sub-Saharan Africa to corroborate these findings has remained sparse. What exists is speculative and at best anecdotal. Using data from construction firms in Uganda, this study finds that commitment to the project, perceived value of the project, interorganizational cooperation, and opportunistic behavior are significant predictors of contractor performance. This has both policy and managerial implications, which we present in this paper.
Keywords: construction, contractor performance, interorganizational relationships, opportunistic